1995
DOI: 10.1111/j.1525-1470.1995.tb00116.x
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Erythromycin‐Resistant Staphylococcus aureus in Impetiginized Dermatoses

Abstract: A trend toward increasing resistance of Staphylococcus aureus to standard antibiotic therapy has been reported. Specimens were taken from 98 patients in our outpatient staff clinic who had clinical signs of superficial skin infections. Patients with erythromycin-resistant S. aureus were contacted by telephone or seen in clinic. The organism was found in 87% of patients. Twenty-two (26%) of the 85 cultures that grew S. aureus were resistant to erythromycin. Treatment failure occurred in one of these patients. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 13 publications
1
3
0
1
Order By: Relevance
“…Results revealed that there is an inverse relationship between the percentage of isolated S. aureus and patient age. Similar patterns of these results were observed in different studies conducted in Iraq and worldwide [18,19].…”
Section: Discussionsupporting
confidence: 78%
“…Results revealed that there is an inverse relationship between the percentage of isolated S. aureus and patient age. Similar patterns of these results were observed in different studies conducted in Iraq and worldwide [18,19].…”
Section: Discussionsupporting
confidence: 78%
“…In earlier reports, Streptococcus pyogenes was considered to be the primary etiological agent, with staphylococcus being a secondary invader [14]. However, more recent studies have shown that up to 87% of impetigo cases are due to Staphylococcus aureus and not Streptococcus pyogenes [15]. This apparent shift of pathogen from Group A streptococci to Staphylococcus aureus has remained unexplained, but it has been documented in different countries [16,17], and it may have played a key role in changing the paradigm of APSGN.…”
Section: Discussionmentioning
confidence: 99%
“…[20] Erythromycin resistance has been found to vary from 3% to 74% in S. aureus [12] and more so in S. pyogenes in different studies from across the world, which makes it unsuitable for empirical treatment of SSTIs in children. [21] In a community-based study of pyoderma from India, prevalence of erythromycin-resistant strains of S. aureus was found to be 56.4%. [8] Both S. aureus and streptococci may show resistance to MLS agents (macrolide, lincosamide, streptogramin B), which is mediated by methylation of 23SrRNA, inhibiting effective ribosomal binding of the antibacterials.…”
Section: Epidemiologymentioning
confidence: 99%